2012 IEEE Intelligent Vehicles Symposium 2012
DOI: 10.1109/ivs.2012.6232121
|View full text |Cite
|
Sign up to set email alerts
|

ACC of electric vehicles with coordination control of fuel economy and tracking safety

Abstract: An adaptive cruise control system of electric vehicles is proposed, considering both fuel economy and tracking safety with model predictive control theory. Firstly, the mathematical relationship between fuel cost and longitudinal acceleration is analyzed through a simulation model. Secondly the 2-norm number is adopted to indicate the integrated cost function, which integrates economy performance and tracking performance together. Finally the proposed optimization problem is solved by model predictive control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…In [49], the conditions of EV safety tests are analyzed in terms of protecting people inside the vehicle in frontal, side, and rear collisions, and specific aspects for such vehicles in the electrical aspect are indicated. Similar issues are considered in [50][51][52]. The work [53] also paid attention not only to the technical side of crash tests for EV assessments but also to the safety of employees and research infrastructure, proposing a set of appropriate procedures for this purpose.…”
Section: Review Of Ev Safety Issuesmentioning
confidence: 99%
“…In [49], the conditions of EV safety tests are analyzed in terms of protecting people inside the vehicle in frontal, side, and rear collisions, and specific aspects for such vehicles in the electrical aspect are indicated. Similar issues are considered in [50][51][52]. The work [53] also paid attention not only to the technical side of crash tests for EV assessments but also to the safety of employees and research infrastructure, proposing a set of appropriate procedures for this purpose.…”
Section: Review Of Ev Safety Issuesmentioning
confidence: 99%
“…According to simulation results of Kim et al, 31 tracking performances of these two methods do not have big differences, while LQR control requires much less computation effort. Another study 34 find in real vehicle test that MPC can save more than 5% energy compared with LQR.…”
Section: Hierarchical Controllermentioning
confidence: 99%
“…MPC is able to balance different performance indicators and incorporate constraints effectively within a cost function. A study showed that MPC consumes 5% less fuel when compared with LQR during road tests [3]. In addition, based on online optimization of the cost function in every time step, MPC is much more robust against disturbances such as rapid traffic condition changes like the cut-in of another vehicle when compared with LQR.…”
Section: Introductionmentioning
confidence: 99%